Boko Haram, islamist protest, and national security - Chétima, Melchisedek; Lovejoy, Paul E. (Africa World Press, 2024)
"Boko Haram, Islamic Protest, and National Security highlights one of the most serious problems of the contemporary world order - ideologically and religious motivated violence. Terrorist movements like Boko Haram represent a challenge to an understanding of contemporary Islam, distorted economic and political development, and the injustices of the international world order. The resonance between local conditions and trans-national problems raises serious issues of public policy and national security. These problems are perceived in religious terms that have dangerous consequences in terms of perceptions of Islam that undermine efforts to promote multicultural societies and peaceful interaction globally. Contributors to the volume approach the phenomenon 'from below' by relying on primary sources, aiming to exhume the underlying roots of Boko Haram and present recommendations to generate effective policies."--Back cover